2015
DOI: 10.1073/pnas.1511780112
|View full text |Cite
|
Sign up to set email alerts
|

How osmolytes influence hydrophobic polymer conformations: A unified view from experiment and theory

Abstract: It is currently the consensus belief that protective osmolytes such as trimethylamine N-oxide (TMAO) favor protein folding by being excluded from the vicinity of a protein, whereas denaturing osmolytes such as urea lead to protein unfolding by strongly binding to the surface. Despite there being consensus on how TMAO and urea affect proteins as a whole, very little is known as to their effects on the individual mechanisms responsible for protein structure formation, especially hydrophobic association. In the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
155
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 119 publications
(163 citation statements)
references
References 62 publications
8
155
0
Order By: Relevance
“…Such a result suggests that TMAO is actually enriched rather than depleted at hydrophobic interfaces. This finding is consistent with previous measurements (3,17,31), although it is perhaps puzzling given the fact that TMAO is nearly as effective as glycine at depressing the LCST of the ELP (Fig. 3A).…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…Such a result suggests that TMAO is actually enriched rather than depleted at hydrophobic interfaces. This finding is consistent with previous measurements (3,17,31), although it is perhaps puzzling given the fact that TMAO is nearly as effective as glycine at depressing the LCST of the ELP (Fig. 3A).…”
Section: Resultssupporting
confidence: 92%
“…Interestingly, Berne and coworkers (17,18) have recently observed similar results for hydrophobic polymers, such as polystyrene and simulated polymers of uncharged Lennard-Jones beads. In particular, they suggested that TMAO accumulates at the surface of extended hydrophobic polymers but still stabilizes collapsed conformations, because TMAO accumulates to an even greater extent at the surface of the collapsed polymer (17,18).…”
Section: Resultsmentioning
confidence: 65%
See 3 more Smart Citations